The Impact of Students' Vocabulary Mastery by Using Memrise Application in Senior High School 6 Muaro Jambi - Dameria. H, Yohana Aprillia; Dewi, Kartika (Universitas Batanghari Jambi, 2024)
Vocabulary is important to support the four English skills, such as reading, writing, listening and speaking. Writing is one of the skills of organizing information or opinion in written form. Writing is one of the skills closely related to vocabulary learning. Writing as a thinking process involves a student’s ability to organize words and explain them in writing. In other words, without vocabulary, students cannot write well and communicate their ideas. This research is a type of quantitative research that uses experiments. The experimental method is carried out to see the effect of a treatment. The purpose of quantitative statistics is to test hypotheses. The population of this study amounted to 8 classes consisting of 180 students. The researcher selected class XA as the sample in this study, which consisted of 30 students. There is a difference in learning outcomes of English vocabulary learning between the experimental group using the Memrise application and the control group taught without using the Memrise application as evidenced by the experimental group data with a sig value, (2-tailed) = 0.001 while sig 0.05 then (0.001 <0.05) then ha is accepted, this shows that there is a significant increase in the mastery of student vocabulary using the Memrise application at SMA Negeri 6 Muaro Jambi Academic Year 2024.